1987
DOI: 10.1128/jb.169.2.640-645.1987
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of genes determining receptor binding and pilus length of Escherichia coli type 1 pili

Abstract: We describe the identification and characterization of two genes and their gene products responsible for determining receptor binding and pilus length in type 1-piliated Escherichia coli. One gene, pilE, conferred the ability of piliated cells to agglutinate guinea pig erythrocytes. The other gene, pilF, determined pilus length, in that mutants having lesions in pilF had very long pili. The two genes were detected after TnS mutagenesis of a cloned segment of DNA that normally complemented a pilE lesion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 19 publications
6
86
1
Order By: Relevance
“…analogous to the various adhesins a.,soci;tted L+I'!? c!lfTerent E. coli pili (Lindberg et al, 1986;Moch et d., 1987;Maurer & Orndorff, 1987;Abraham et af., 1987). Further studies of A .…”
Section: Resultsmentioning
confidence: 99%
“…analogous to the various adhesins a.,soci;tted L+I'!? c!lfTerent E. coli pili (Lindberg et al, 1986;Moch et d., 1987;Maurer & Orndorff, 1987;Abraham et af., 1987). Further studies of A .…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pJP4 encodes the E. coli type 1 fimbrial chaperone, FimC (15,24). The properties of each of these plasmids have been described in detail elsewhere (15,17,(21)(22)(23)(24) (26). The ( 14,15).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that type 1 fimbriae promote bacterial binding and activation of different immunoinflammatory cells such as lymphocytes and neutrophils, evoking a variety of biological reactions in the activated cells ( 14,15). The determinant of adherence and host cell activation on type 1 fimbriae is a minor protein, FimH, which is located in a functionally competent configuration at the tips of each fimbrial filament (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1,000 copies of the 17-kDa primary structural subunit, FimA (or PilA), are polymerized into a right-handed helical fibril also containing minor amounts of the FimF, FimG, and FimH subunits (20,24,27,32). The 28-kDa FimH subunit has been shown by direct and indirect tests to be the fimbrial lectin (1-3, 20, 21, 27, 29, 32, 36, 55).…”
mentioning
confidence: 99%